ANALISIS PENILAIAN HARGA SAHAM MENGGUNAKAN METODE DIVIDEND DISCOUNT MODEL (DDM) SEBAGAI DASAR PENGAMBILAN KEPUTUSAN INVESTASI (Studi pada Perusahaan yang termasuk dalam Indeks LQ-45 di Bursa Efek Indonesia Tahun 2013-2015) - Vandara Vavras Setia (Faculty of Social and Political Science, 2017)
LQ-45 is a group share consisting of 45 shares of the elect with the level of market capitalization and liquidity level above the average for the other stocks. So LQ-45 became one of the most volatile due to the high level of liquidity and market activities. The share price berfluktuatif is a risk that must be faced by investors. Assessment of the share price can be done to minimize the risk of one price. This research aims to know and analyze the results from the calculation of the stock valuation using the Dividend Discount Model (DDM) as the basis for decision on investment companies including in the LQ-45 in Indonesia Stock Exchange the year 2013-2015. This research is classified as quantitative descriptive research and sampling used is purposive sampling. A sample of this research as much as 11 companies in accordance with the criteria. Based on the results of research and analysis of the data using the method Dividend Discount Models (DDM) not constant growth shows that the entire company in 2015 including overlavued category among others, ADRO, AKRA, ASII, ( BBCA, BBNI, BBRI, BMRI, CPIN, GGRM, UNTR, UNVR. While, 2013 and 2014 only one company including undervalued categories namely ASII. Investment decision that can be taken when have stocks including overvalued category, should be sold and when the shares including undervalued categories should be purchased or suspended when has.